2014
DOI: 10.1371/journal.pone.0099337
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Developmental Dyslexia Subtypes: Heterogeneity of Mixed Reading Profiles

Abstract: We examined whether classifications based on reading performance are relevant to identify cognitively homogeneous subgroups of dyslexic children. Each of the 71 dyslexic participants was selected to have a mixed reading profile, i.e. poor irregular word and pseudo-word reading performance (accuracy and speed). Despite their homogeneous reading profile, the participants were found to split into four distinct cognitive subgroups, characterized by a single phonological disorder, a single visual attention span dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
121
3
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(144 citation statements)
references
References 72 publications
7
121
3
10
Order By: Relevance
“…In other words, do cross-linguistic variations also affect auditory phonology and visual attention span skills? Both phonological decoding and whole-word reading strategies require the contribution of auditory and visual processes (Zoubrinetzky, Bielle, & Valdois, 2014), but via different grain size: The latter strategy particularly taxes the system's sensitivity to small auditory and visual grains (single-element units), whereas the former would rely on larger grains (multi-element chunks). Consequently, it is reasonable to assume that optimal grain sizes for auditory phonological processing and visual attention span also vary as a function of orthographic depth.…”
Section: The Impact Of Orthographic Depth On the Auditory And Visual mentioning
confidence: 99%
“…In other words, do cross-linguistic variations also affect auditory phonology and visual attention span skills? Both phonological decoding and whole-word reading strategies require the contribution of auditory and visual processes (Zoubrinetzky, Bielle, & Valdois, 2014), but via different grain size: The latter strategy particularly taxes the system's sensitivity to small auditory and visual grains (single-element units), whereas the former would rely on larger grains (multi-element chunks). Consequently, it is reasonable to assume that optimal grain sizes for auditory phonological processing and visual attention span also vary as a function of orthographic depth.…”
Section: The Impact Of Orthographic Depth On the Auditory And Visual mentioning
confidence: 99%
“…http://dx.doi. org/10.1038/nrn3836-c1 (2015)) 2 , Lobier and Valdois bring together 12 of their studies to argue that a visual attention (VA) span deficit meets the criteria that are required to demonstrate causality in developmental dyslexia [3][4][5][6][7][8][9][10][11][12][13][14] . Unfortunately, all of the studies that were discussed used letters to assess VA span; thus, the demonstrated deficit only affects letters and is causally ambiguous , as the individuals with dyslexia and control individuals that were studied differed dramatically in their experience of recoding letters to sound.…”
mentioning
confidence: 99%
“…Lobier and Valdois report an RL match study with 10-year-old children with dyslexia and 7-year-old typically developing children 7 . The VA span deficit (in letter report) was significant, but the younger children were markedly poorer at identifying single letters, which were the stimuli used in the VA span task.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This way, we could hypothesize that voiceless/voiced interchanges are a manifestation of alteration in auditory temporal processing. This hypothesis is strengthened by evidence that this kind of misspelling is more frequent in oralized deaf and dyslexic individuals (Zoubrinetzky et al, 2014), for whom the alteration in auditory temporal processing is well documented.…”
Section: The Contribution Of Evidences On Changes In Auditory Processmentioning
confidence: 96%